A potential role of endogenous progesterone in modulation of GH, prolactin and thyrotrophin secretion during normal menstrual cycle - Caufriez, Anne; Leproult, Rachel; L'Hermite-Balériaux, Mireille; Moreno-Reyes, Rodrigo; Copinschi, Georges (Clinical endocrinology (Oxford), 2009)
Summary Objective  Previous studies investigating the fluctuations of endocrine secretion across the menstrual cycle yielded inconsistent results. Our objective was to evaluate during the menstrual cycle the potential role of endogenous oestradiol and progesterone in the regulation of hormones primarily controlled by the circadian clock and/or the sleep‐wake cycle. Subjects and design  Ten normally cycling young lean women were investigated once during follicular and once during luteal phase. Sleep was polygraphically recorded, and blood samples were obtained at 20‐min intervals for 24 h. Results  Sleep variables and diurnal melatonin and cortisol profiles (hormones primarily controlled by the circadian clock) were similar in both conditions. The TSH evening rise (a circadian marker) was similar in both conditions, but the sleep‐related nocturnal TSH decrease occurred earlier during the luteal phase (P = 0·03) and tended to correlate positively with progesterone levels (rs = −0·64, P < 0·06). Daytime GH secretion and afternoon/evening PRL secretion (hormones primarily controlled by the sleep‐wake homeostasis) were increased in the luteal phase compared with those of the follicular phase (GH: P = 0·04; PRL: P = 0·01). The increase in 24‐h GH secretion was associated with higher progesterone levels (rs = 0·78, P = 0·02). In luteal phase, the evening PRL rise was associated with higher progesterone (rs = 0·70, P = 0·04) and oestradiol (rs = 0·72, P = 0·03) levels. Conclusion  The present data indicate that in normally cycling young women, daytime GH and PRL secretions are increased in luteal phase. These data also suggest that endogenous progesterone could play a modulation role on pituitary hormone secretion, stimulating GH and PRL release and enhancing the inhibitory action of sleep on TSH secretion.